2020
DOI: 10.1371/journal.pone.0236133
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of gut hormone and metabolic changes after laparoscopic sleeve gastrectomy and Roux-en-Y gastric bypass

Abstract: Background Laparoscopic sleeve gastrectomy (SG) has surpassed Roux-en-Y gastric bypass (RYGB) as the most prevalent bariatric procedure worldwide. While RYGB and SG demonstrate equivalent short-term weight loss, long-term weight loss tends to be greater after RYGB. Differences in the effect of these procedures on gastrointestinal hormones that regulate energy homeostasis are felt to partially underlie differences in outcomes. The objective of this study was to prospectively quantify blood levels of gut hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 58 publications
4
34
1
Order By: Relevance
“…Alterations in PYY levels after bariatric surgery [21,32,34,45,83,85,89,91,94,108,114] are described in Table 1. Postprandial PYY levels are elevated after RYGB and SG, with more potent changes after RYGB [34,91,108,114].…”
Section: Pyymentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in PYY levels after bariatric surgery [21,32,34,45,83,85,89,91,94,108,114] are described in Table 1. Postprandial PYY levels are elevated after RYGB and SG, with more potent changes after RYGB [34,91,108,114].…”
Section: Pyymentioning
confidence: 99%
“…Fasting ↓ [85,87,88,90] or ↔ [33,34,48,88,89,91,92.94,108,114] or ↑ [86][87][88]91,108] Postprandial ↓ [48,85,90] or ↔ [33,34,48,89,94,108,114] or ↑ [89,91] Fasting ↓↓ [23,33,34 [23,33,97,119] Fasting ↔ [23,33] Postprandial ↔ [23] or ↑ [33] Fasting ↔ [33] Postprandial NA…”
Section: Ghrelinmentioning
confidence: 99%
“…Hence, the authors of this study hypothesized that the increase in oxytocin levels induced by probiotic treatment contributed to the improvement in weight management [ 204 ]. Taken together, it can be concluded that studies show inconsistent changes in oxytocin levels following weight reduction, which could be related the different hormonal/metabolic changes associated with each method of bariatric surgery [ 206 ] and the independent mechanisms related to the interaction of probiotic treatment with oxytocin [ 205 ].…”
Section: Observational Studies In Humans-relation Of Oxytocin To Food Intake Weight Status and Metabolismmentioning
confidence: 99%
“…Because RYGB mainly reduces fat mass [ 33 ], it is associated with a marked reduction in circulating leptin levels [ 34 , 35 , 36 ]—even beyond chronic caloric restriction-induced weight loss alone [ 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, endogenous leptin action has been proposed to be enhanced postoperatively [ 43 , 44 , 45 , 46 , 47 , 48 ], thereby preventing the powerful counter-regulatory response to depletion of energy stores which normally leads to weight-regain [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%